การพัฒนานวัตกรรมกล่องการเรียนรู้ศิลปะจากวัสดุเหลือใช้เพื่อส่งเสริมทักษะการสร้างสรรค์ทางศิลปะสำหรับนักเรียนประถมศึกษา - ปฏิพล พาด้วง (จุฬาลงกรณ์มหาวิทยาลัย, 2023)
This research aims to develop and examine the effects of using an innovative art learning box made from recycled materials to enhance creative art skills for elementary school students. The study follows a Research and Development (R&D) approach, divided into two phases. Phase 1 involves data collection, design, and innovation development by gathering information from relevant literature and research, along with interviews with experts in three areas: 5 experts in developing learning boxes, 5 experts in organizing art activities with recycled materials, and 5 experts in teaching art at the elementary school level. Phase 2 focuses on studying the outcomes of using the innovation with a sample group consisting of 26 primary school students and their teachers. The research tools include learning activity plans, satisfaction surveys for students and teachers, group discussion transcripts for students, and an innovation assessment by experts. Data analysis is conducted quantitatively, calculating averages and percentages, as well as qualitatively through content analysis.The research findings indicate that the development of innovative art learning boxes from recycled materials effectively promotes creative skills and artistic creativity for elementary school students. The approach involves three activity boxes focusing on collage, printmaking, and sculpting, encouraging the use of nearby recycled materials to create artistic works. The development of creative skills through art activities and recycled materials serves as a valuable resource for teaching in small schools with a shortage of art teachers. Recommendations for implementing the learning box innovation in teaching activities include: 1) Stimulating student interest through activities like games or music, 2) Clearly explaining the use of the learning box in teaching activities, 3) Flexible learning activity organization tailored to students, and 4) Evaluating outcomes based on real experiences, considering both the process and what students learn. The assessment of satisfaction with the learning box activities among elementary school students reveals an overall high level of satisfaction (Mean = 2.95), with the highest satisfaction in student development (Mean = 2.98), teaching and learning box activities (Mean = 2.94), and the characteristics of the learning box (Mean = 2.94). Group discussions indicate that students appreciate art activities using recycled materials due to cost-effectiveness and the opportunity to creatively use readily available materials, finding it enjoyable and interesting when incorporating learning boxes into their education.